Regional patterns of intangible capital, agglomeration effects and localised spillovers in Germany - Kurt Geppert; Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We use a large micro-dataset to assess the importance of intangible capital - organisation, R&D and ICT capital - for the economic performance of establishments and regions in Germany. In 2003 self-produced intangible capital accounted for more than one fifth of the total capital stock of estab-lishments. More than half of the intangible capital is R&D capital. This high proportion is mainly due to a relatively strong and research-intensive manufacturing sector in Germany. At the regional level, we find descriptive evidence for a positive relationship between intangible capital and the economic performance of regions. This is true both for the level of economic activities and for growth. The results of cross-sectional regressions for the years from 1999 to 2003 indicate that dou-bling the intangible capital intensity of establishments increases the average wage levels by one percent. Regarding the regional economic environment of establishments, we find that the substan-tial net advantages of agglomeration have more to do with broad knowledge and diversity than with regional clustering and specialisation. Separate regressions for the wage levels of non-intangible workers show very similar results. These workers can share the rents of the activities of intangible workers. Thus, intangible capital generates positive externalities not only at the regional level, but also at the level of establishments.
Keywords: J24; M40; O33; R30; 330; firm productivity; intangible capital; agglomeration; local spillovers; Immaterielles Anlagevermögen; Industrielle Forschung; Produktivität; Lohnniveau; Unternehmensentwicklung; Regionale Entwicklung; Agglomerationseffekt; Spillover-Effekt; Deutschland